THE INFLUENCE OF LEADERSHIP STYLE, ORGANIZATIONAL CULTURE, AND INDEPENDENCE ON THE PERFORMANCE EFFECTIVENESS OF AUDITORS OF FINANCIAL AND DEVELOPMENT SUPERVISION AGENCY WITH ORGANIZATIONAL COMMITMENT AS MEDIATION - Wulansari, Safitri Dwi; sopian, sopian (IPSAR (International Public Sector Accounting Review), 2024)
The efficient control of corruption and financial accountability at the state or regional level mostly relies on internal supervision that is effective. To guarantee maximum effectiveness in its supervisory role, the Financial and Development Supervisory Agency, serving as the Government Internal Supervisory Apparatus, is committed to improving auditor performance. Both external and internal factors can influence the effectiveness of auditor performance, such as auditor independence, organizational culture, and leadership style. This study delves into how these factors impact auditor performance through the lens of organizational commitment as a mediating variable. Using survey data collection techniques, the research methodology is quantitative. The study was conducted at the Financial and Development Supervisory Agency, with 228 respondents selected through convenience sampling. Data analysis was carried out using the smartPLS.3.0 application. The results of the study indicate that leadership style, organizational culture, and independence have a significant effect on the effectiveness of auditor performance at the Financial and Development Supervisory Agency. Moreover, organizational commitment is identified as a mediator that can influence the relationship between the aforementioned factors and the effectiveness of auditor performance